Initial Studies of the Response of Rubber Tree Seedlings Treated with Saprobic Fungi from the Semiarid Region of Northeast Brazil to Anthracnose - Bergamini Lopes, Marcela Pagoti [UNESP]; Gomes, Marcela Eloi [UNESP]; Celin, Gustavo da Silva [UNESP]; Bello, Heloisa Noemi [UNESP]; Pinheiro Henrique, Rodney Lucio [UNESP]; Magalhaes, Izabela Ponso [UNESP]; Santos, Louyne Varini [UNESP]; Tropaldi, Leandro [UNESP]; Pascholate, Sergio F.; Furtado, Edson Luiz [UNESP]; Firmino, Ana Carolina [UNESP] (Mdpi, 2022)
Anthracnose, caused by fungi of the genus Colletotrichum, is present in the main areas where rubber trees (Hevea brasiliensis) are planted. Thus, considering that biological agents can be an alternative for disease control, the present study aimed to carry out initial studies to investigate the response of rubber tree seedlings inoculated with Colletotrichum and treated with saprobes fungi from the semiarid region of Northeast Brazil (Curvularia eragrostidis, Memnoniella levispora, Myrothecium roridum and Phialomyces macrosporus). Seedlings of the rubber tree clone RRIM600 were sprayed with biocontrol agents as preventive and curative treatments seven days before and after C. tamarilloi inoculation, respectively. Assessments included plant response to disease expression based on the percentage of symptomatic area on treated leaves, percentage of graft death, and percentage of apical death in seedlings 30 days after inoculation with C. tamarilloi. In addition, the enzymes peroxidase and phenylalanine ammonia lyase (PAL) had their activity quantified by their association with plant resistance to pathogens. The fungus C. eragrostidis had the best result in controlling anthracnose when applied as a preventive treatment, showing 10% less disease than the untreated plant. The same was observed for the fungus P. macrosporus when used in the curative form. These fungi also reduced the graft death. In these cases, PAL activity was higher and may be linked to the induction of resistance against the pathogen. The peroxidase activity was not expressive for treatments with saprobic fungi in the periods studied. Therefore, among the tested fungi, C. eragrostidis and P. macrosporus are promising for the control of anthracnose, deserving further studies.
Keywords: Colletotrichum; Hevea brasiliensis; control; resistance induction